Application of virtual synchronous generator technology in power systems and its modeling in the Matlab software package - R. R. Sattarov; R. R. Garafutdinov (Известия высших учебных заведений: Проблемы энергетики)
Currently, the commissioning of power plants based on renewable energy sources (RES) using inverters is becoming widespread. However, these power plants do not participate in maintaining the stability of the power system during emergency disturbances, since they are switched off by technological protections when a disturbance occurs. In the future, when power plants based on renewable energy sources become widespread, ensuring the possibility of their participation in maintaining sustainability will significantly increase the reliability of the energy system. A preliminary assessment of the effectiveness of participation in maintaining sustainability should be carried out through computer modeling.THE PURPOSE: To realize the possibility of participation of RES-based power plants in ensuring reliable and sustainable operation of the power system, as well as to realize the possibility of performing a preliminary assessment of the effectiveness of the proposed method.METHODS. In this paper, the application of virtual synchronous generator technology is proposed to realize the possibility of participation of RES-based power plants in ensuring the reliability and sustainability of the power system. Also, a method of modeling the virtual synchronous generator in Matlab software package is proposed.RESULTS. The technology of virtual synchronous generator is proposed, which with the use of inverter, electric energy storage and appropriate control system can provide the increase of dynamic stability of power system. A method of modeling the virtual synchronous generator in Matlab software package is proposed. The results obtained allow us to conclude that the constructed model of a virtual synchronous generator is efficient, maintains the stability of the system and ensures correct control of the inverter, as a result of which the parameters of the electrical network are maintained within acceptable limits. The resulting computer model can be used in further research.CONCLUSION. The technology of virtual synchronous generator allows to imitate in the inverter the inertial and damping characteristics of the traditional synchronous generator, and the proposed computer model will help to evaluate the effectiveness of this technology when implemented in the power system.